Lactobacillus rossiae, a Vitamin B(12) Producer, Represents a Metabolically Versatile Species within the Genus Lactobacillus - De Angelis, Maria (Public Library of Science, 2014)

(untitled)
Lactobacillus rossiae is an obligately hetero-fermentative lactic acid bacterium, which can be isolated from a broad range of environments including sourdoughs, vegetables, fermented meat and flour, as well as the gastrointestinal tract of both humans and animals. In order to unravel distinctive genomic features of this particular species and investigate the phylogenetic positioning within the genus Lactobacillus, comparative genomics and phylogenomic approaches, followed by functional analyses were performed on L. rossiae DSM 15814(T), showing how this type strain not only occupies an independent phylogenetic branch, but also possesses genomic features underscoring its biotechnological potential. This strain in fact represents one of a small number of bacteria known to encode a complete de novo biosynthetic pathway of vitamin B(12) (in addition to other B vitamins such as folate and riboflavin). In addition, it possesses the capacity to utilize an extensive set of carbon sources, a characteristic that may contribute to environmental adaptation, perhaps enabling the strain's ability to populate different niches.